The Influence of the Labor Force and Regional Income on the Human Development Index (HDI) in Indonesia - Situmorang, Elsa Aurel Agustine; Deyren, Deyren Firmansyah; Meutia , Meutia Fahrani; Novianti , Novianti Naomi Ulina Br Naibaho; Chia Yu (Outline Publisher, 2024)
This research examines the influence of the labor force and regional income on the Human Development Index (HDI) in Indonesia during 2012-2022. Using panel data analysis and multiple regression, the results show that the labor force has a significant positive influence on HDI, while regional income shows a negative influence. This shows that increasing the workforce contributes to improving the quality of life, but regional income without effective management does not always improve human development. These findings are important for policy makers in managing the workforce and regional income to achieve a higher HDI.